2010
DOI: 10.1002/ijc.25234
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency or blockade of angiotensin II type 2 receptor delays tumorigenesis by inhibiting malignant cell proliferation and angiogenesis

Abstract: Despite significant expression level in cancer cells, the role of the angiotensin II Type 2 receptor (AT2R) in cancer progression remains poorly understood. We aimed to investigate the involvement of AT2R in tumorigenesis, hypothesizing a role in tumor cell proliferation and/or tumor angiogenesis. Two animal tumor models were used: fibrosarcoma induced by 3-methylcholanthrene (3-MCA) in FVB/N mice invalidated for AT2R (AT2R-KO) and carcinoma LL/2 cells injected in C57BL/6N mice treated with AT2R antagonist PD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 39 publications
(52 reference statements)
3
50
0
Order By: Relevance
“…However, type 2 receptor activation would be expected to have antitumor effects, 28 -31 although data are somewhat conflicting. 27,32 Safety studies in animals have also demonstrated the absence of carcinogenicity with high doses of ARBs. [33][34][35][36][37][38][39] Some strengths and limitations of our large nationwide cohort study deserve particular mention.…”
Section: Discussionmentioning
confidence: 99%
“…However, type 2 receptor activation would be expected to have antitumor effects, 28 -31 although data are somewhat conflicting. 27,32 Safety studies in animals have also demonstrated the absence of carcinogenicity with high doses of ARBs. [33][34][35][36][37][38][39] Some strengths and limitations of our large nationwide cohort study deserve particular mention.…”
Section: Discussionmentioning
confidence: 99%
“…AT 1 R-mediated proangiogenic effect can be triggered by HIF-1α (57). Deficiency or blockade of AT 2 R-inhibited tumor angiogenesis by impairing VEGF expression in murine fibrosarcoma and Lewis lung carcinoma (58). Whether AT 2 R activation exerts beneficial or detrimental effects on tumor angiogenesis needs further studies.…”
Section: Discussionmentioning
confidence: 99%
“…ARBs, in turn, selectively block the angiotensin II type 1 receptors, responsible for vasoconstriction, cell growth, and sympathetic activation and in this way exerts their potential antineoplastic effect, maintaining the beneficial effects of angiotensin II type 2-receptor stimulation (vasodilatory and antiproliferative action mediated via the kinin system) [21,37]. Nevertheless, some studies have suggested a pro-tumoral effect of the ARBs as a result of the stimulation of free angiotensin II type 2-receptor, which results in increased tumor progression [18,43,44].…”
Section: Accepted Manuscriptmentioning
confidence: 99%